A NOTE ON THE GROWTH OF PENAEUS MONODON FABRICIUS IN A RAIN-FED COASTAL POND IN SUNDERBANS - Pillai, S M; Ghosh, P K; Rajyalakshmi, T; Halder, D D; Roy, A K; Chakraborty, R K (Indian Journal of Fisheries, 2011)
Polyculture of Penaeus monodon, along with freshwater carps, mullets and milk fish, was undertaken in a rain-fed pond to study the growth and survival in freshwater conditions in coastal areas. In two consecutive experiments during 1978 and 1979 the prawns showed relatively faster growth, attaining 60-65 g in 4 months and 70-80 g in 7-8 months of culture. However, survival of the prawns was poor, maximum being 34.6%.